Quality of life in personal social ecosystems: Further psychometric evaluation and Hungarian adaptation of the Experience in Personal Social Systems Questionnaire (European Journal of Mental Health, 2022)
Introduction: Hunger et al. (2014, 2015, 2017) developed the Experience in Personal Social Systems Questionnaire (EXIS.pers) to assess individuals’ perceived functioning in their personal ecosystems.Aims: The present study aims to 1) provide further data regarding this instrument’s psychometric characteristics that have not yet been investigated, as well as 2) describe the scale’s Hungarian adaptation.Methods: The present data set consisted of 400 questionnaires of 182 individuals recruited from the general population (83.8% female, Mage = 39.8 years, SDage = 9.3 years) participating in repeated assessments. The Brief Symptom Inventory, the SCOFF screening test, the Patient Health Questionnaire-15, the Meaning in Life Questionnaire, and the WHO Wel-being Index were used to investigate construct validity.Results: A bifactor structure of the EXIS.pers fitted the data best according to the confirmatory factor analytic models. The results confirmed the scalar invariance of the best fitting bifactor model across both sex and time.Internal consistency of both the subscale and total scores was good according to both traditional (Cronbach’s alpha) and more advanced (omega) indicators. Test-retest reliability with one- and five-month time lag was appropriate, as well. EXIS.pers scores showed significant inverse association with all 13 indicators of psychopathology and positive associations with both indicators of positive mental health suggestive of appropriate validity.Conclusions: The results indicate that the EXIS.pers can be used with confidence when comparing men and women or in studies involving repeated measures designs, and that the Hungarian version serves as a reliable and valid adaptation of the original instrument.